Non-covalent versus covalent donor-acceptor systems based on near-infrared absorbing azulenocyanines and C 60 fullerene derivatives - Ince, Mine; Hausmann, Anita; Victoria Martinez-Diaz, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2012)
A novel supramolecular electron donor-acceptor hybrid (2·1) and an electron donor-acceptor conjugate (3), both exhibiting a remarkably shifted Q band in the NIR region of the solar spectrum, were prepared. Irradiation of the supramolecular ensemble 2·1 within the visible range leads to a nanosecond lived radical-ion pair state Zn-azulenocyanine -C . © 2012 The Royal Society of Chemistry.